Insights into Magnetic Interactions in a Monodisperse Gd12Fe14 Metal Cluster. (9th August 2017) - Zheng, Xiu‐Ying; Zhang, Hui; Wang, Zhenxing; Liu, Pengxin; Du, Ming‐Hao; Han, Ying‐Zi; Wei, Rong‐Jia; Ouyang, Zhong‐Wen; Kong, Xiang‐Jian; Zhuang, Gui‐Lin; Long, La‐Sheng; Zheng, Lan‐Sun
Abstract: The largest Ln–Fe metal cluster [Gd12 Fe14 (μ3 ‐OH)12 (μ4 ‐OH)6 (μ4 ‐O)12 (TEOA)6 (CH3 COO)16 (H2 O)8 ]⋅(CH3 COO)2 (CH3 CN)2 ⋅(H2 O)20 (1 ) and the core–shell monodisperse metal cluster of1 a @SiO2 (1 a =[Gd12 Fe14 (μ3 ‐OH)12 (μ4 ‐OH)6 (μ4 ‐O)12 (TEOA)6 (CH3 COO)16 (H2 O)8 ] 2+ ) were prepared. Experimental and theoretical studies on the magnetic properties of1 and1 a @SiO2 reveal that encapsulation of one cluster into one silica nanosphere not only effectively decreases intermolecular magnetic interactions but also significantly increases the zero‐field splitting effect of the outer layer Fe 3+ ions.